2007
DOI: 10.1073/pnas.0705738104
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome c oxidase deficiency in neurons decreases both oxidative stress and amyloid formation in a mouse model of Alzheimer's disease

Abstract: Defects in the mitochondrial cytochrome c oxidase (COX) have been associated with Alzheimer's Disease, in which the agedependent accumulation of ␤-amyloid plays an important role in synaptic dysfunction and neurodegeneration. To test the possibility that age-dependent decline in the mitochondrial respiratory function, especially COX activity, may participate in the formation and accumulation of ␤-amyloid, we generated mice expressing mutant amyloid precursor protein and mutant presenilin 1 in a neuron-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
143
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 168 publications
(150 citation statements)
references
References 44 publications
5
143
1
1
Order By: Relevance
“…To assess whether a genetically induced complex IV deficiency affects oxidative stress and production/accumulation of Aβ, we have first generated neuron-specific conditional COX10 knockout mice and then crossed them with a mouse model of AD to generate complex IVdeficient AD mice (COXd/AD mice) [53]. Contrary to our expectation, brains of COXd/AD mice exhibited less amyloid plaque and reduced Aβ deposition, as compared to AD mice.…”
Section: Contribution Of Complex IV Defects To Oxidative Stress and Nmentioning
confidence: 89%
See 3 more Smart Citations
“…To assess whether a genetically induced complex IV deficiency affects oxidative stress and production/accumulation of Aβ, we have first generated neuron-specific conditional COX10 knockout mice and then crossed them with a mouse model of AD to generate complex IVdeficient AD mice (COXd/AD mice) [53]. Contrary to our expectation, brains of COXd/AD mice exhibited less amyloid plaque and reduced Aβ deposition, as compared to AD mice.…”
Section: Contribution Of Complex IV Defects To Oxidative Stress and Nmentioning
confidence: 89%
“…These studies consistently demonstrated a strong correlation between oxidative stress and accumulation of Aβ with the possible involvement of an APP-processing enzyme, β-secretase [53][54][55][56][57]. A recent report using heterozygous Mn-SOD knockout mice also showed that oxidative stress modulates hyperphosphorylation of tau, which leads to the formation of neurofibrillary tangles [58].…”
Section: Contribution Of Complex IV Defects To Oxidative Stress and Nmentioning
confidence: 93%
See 2 more Smart Citations
“…The COX assembly protein, Cox10, was selectively inactivated in mouse muscle, neurons, and liver (Diaz et al 2005(Diaz et al , 2008Fukui et al 2007). Muscle-specific Cox10-depleted animals develop a regressive myopathy and weakness, starting the age of 3 mo and leading to death at between 4 and 10 mo.…”
Section: Modification Of Ndna Oxphos Genesmentioning
confidence: 99%